Airborne particle dispersion around the feet of surgical staff while walking in and out of a bio-clean operating theatre. Issue 2 (October 2020) - Sunagawa, S.; Koseki, H.; Noguchi, C.; Yonekura, A.; Matsumura, U.; Watanabe, K.; Osaki, M.
Summary: Background: Bacterial contamination by airborne particles is one of the most important factors in the pathogenesis of surgical-site infections. Aim: This study aimed to identify the generation and behaviour of airborne particles around the feet of surgical staff while walking in and out of an operating theatre. Methods: Two physicians and two nurses walked in and out of a bio-clean theatre under laminar airflow, either individually or as a group. The generation and behaviour of airborne particles was filmed using a fine-particle visualization system, and the number of airborne particles per 2.83 m 3 of air was counted using a laser particle counter. Each action was repeated five times, and particle counts were evaluated statistically. Findings: Airborne particles were generated from the floor and by the shoes and gown hems of the participants, whether walking individually or as a group. Numerous airborne particles were generated by the group, and significantly more particles, especially those measuring 0.3–0.5 μm, were carried up to the level of the operating table by the group than by individuals ( P <0.01). Conclusions: The results of this study provide a clearer picture of the dispersion and distribution of airborne particles around the feet of staff walking in and out of an operating theatre. The findings suggest that to reduce the incidence of bacterial contamination and risk of surgical site infections, surgical staff should walk calmly and independently, if possible, near sterile areas.